The Dilemmas Of (Re)Integration Through Occupational Mental Healthcare - Costa, Felizardo Tchiengo Bartolomeu; Justo, José Sterza (Argumentum, 2020)
The aim of this article is to discuss, through a theoretical study, the full social reintegration of mental health service users through occupational therapy and its implications for the issue of suffering produced by capitalism. To do this, authors and theories have been selected that allow us to raise and make historical links between work and mental disorders, as well as the concepts underlying practices in the field of Psychiatric Reform, such as occupational therapy workshops for employment and income generation. The conclusion highlights the great difficulty in reconciling, in the current stage of capitalism, reintegration into work with the production of mental health or with care strategies for those suffering psychologically.